2015
DOI: 10.1002/jbmr.2485
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Androgens on Murine Cortical Bone Do Not Require AR or ERα Signaling in Osteoblasts and Osteoclasts

Abstract: In men, androgens are critical for the acquisition and maintenance of bone mass in both the cortical and cancellous bone compartment. Male mice with targeted deletion of the androgen receptor (AR) in mature osteoblasts or osteocytes have lower cancellous bone mass, but no cortical bone phenotype. We have investigated the possibility that the effects of androgens on the cortical compartment result from AR signaling in osteoprogenitors or cells of the osteoclast lineage; or via estrogen receptor alpha (ERα) sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 50 publications
(67 reference statements)
6
89
2
1
Order By: Relevance
“…In a cohort of men with acquired secondary hypogonadism, whose mean testosterone level was 185 ng/dl, administration of testosterone enanthate increased lumbar spine BMD more than did a placebo (36). Moreover, testosterone administration did bone in male mice (32). In clinical studies, it has been postulated that the effect of androgens on trabecular bone is difficult to detect utilizing biochemical markers of bone resorption because changes in bone resorption markers reflect the effects of gonadal steroids on the entire skeleton, which is mainly composed of cortical bone (31).…”
Section: Discussionmentioning
confidence: 96%
“…In a cohort of men with acquired secondary hypogonadism, whose mean testosterone level was 185 ng/dl, administration of testosterone enanthate increased lumbar spine BMD more than did a placebo (36). Moreover, testosterone administration did bone in male mice (32). In clinical studies, it has been postulated that the effect of androgens on trabecular bone is difficult to detect utilizing biochemical markers of bone resorption because changes in bone resorption markers reflect the effects of gonadal steroids on the entire skeleton, which is mainly composed of cortical bone (31).…”
Section: Discussionmentioning
confidence: 96%
“…Rankl expression has been found upregulated in osteoblasts of ARKO mice, suggesting that the AR in osteoblasts is critical for the suppressive effect of androgens on osteoclast generation and activity (Kawano et al, 2003). Several animal studies have suggested that the AR might be expressed in osteoclasts and exert effects on these cells in vitro (Huber et al, 2001;Mizuno et al, 1994;Pederson et al, 1999;van der Eerden et al, 2002), although it remains controversial whether the AR inhibits osteoclasts directly. Conditional knockout models have demonstrated that ERα in osteoclasts mediates bone resorption in female but not in male mice (Martin-Millan et al, 2010;Nakamura et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, testosterone deficiency independently predicts fracture risk in some populations (13). Perhaps most convincingly, a recent study in mice supports skeletal site-specific effects of estrogens and androgens by showing that targeted deletion of the murine androgen receptor-encoding gene in osteoblast progenitors compromises trabecular but not cortical bone (24). Conversely, complementary studies in men confirm that serum estradiol is positively associated with cortical thickness and inversely associated with cortical porosity, with evidence of a threshold effect on structural bone parameters, as well (25)(26)(27).…”
Section: Unresolved Issues/future Directionsmentioning
confidence: 93%